The Long-Term Results of Three Catheter Ablation Methods in Patients With Paroxysmal Atrial Fibrillation: A 4-Year Follow-Up Study - You, Ling; Zhang, Xiaohong; Yang, Jing; Wang, Lianxia; Zhang, Yan; Xie, Ruiqin (Frontiers in Cardiovascular Medicine, 2021)
Aims: Catheter ablation of paroxysmal atrial fibrillation (PAF) has been shown to be effective and safe. However, recurrence of PAF varies between 10 and 30% for radiofrequency ablation. There have been no reports comparing long-term recurrence rates following radiofrequency ablation, cryoablation, and three-dimensional guided cryoablation plus radiofrequency ablation. The aim of this study was to observe the long-term recurrence rate of PAF when treated by these three catheter ablation methods, and to explore clinical factors that can potentially predict PAF recurrence following catheter ablation. Methods: There were 238 patients involved in this study, including 106 radiofrequency (RF) ablation cases (RF group), 66 cryoablation cases (Freeze group), and 66 cases treated by three-dimensional guided cryoablation combined with radiofrequency ablation (Freeze-plus-RF group). All patients underwent standardized follow-up. The recurrence rate of atrial fibrillation (AF) in the three groups was calculated. Predictive factors for the recurrence of AF were also investigated. Results: At 48 months (the median follow-up period), the sinus rhythm maintenance rate was 77.4% in the RF group, 72.7% in the Freeze group, and 81.8% in the Freeze-plus-RF group. The maintenance rate of sinus rhythm was highest in the Freeze-plus-RF group, but differences among the three groups were not statistically significant. Further analysis found that the preoperative left atrial appendage emptying velocity (LAAEV) (recurrence vs. no recurrence, 56.58 ± 18.37 vs. 65.59 ± 18.83, respectively, p = 0.003), left atrial (LA) anteroposterior dimension (recurrence vs. no recurrence, 36.56 ± 4.65 vs. 35.00 ± 4.37, respectively; p = 0.028), and LA vertical dimension (recurrence vs. no recurrence, 56.31 ± 6.96 vs. 53.72 ± 6.52, respectively; p = 0.035) were related to postoperative recurrence. Multiple Cox regression analysis showed that only LAAEV was predictive of postoperative recurrence of PAF (hazard ratio: 0.979; 95% confidence interval: 0.961–0.997). Conclusion: Our study found that there was no statistically significant difference in long-term recurrence rates among the RF, Freeze, and Freeze-plus-RF groups. Preoperative LAAEV is an independent predictor of postoperative recurrence of PAF.